One’s Heaven Can Be Another’s Hell: A Mixed Analysis of Portuguese Nationalist Fanpages - Branco Di Fátima; José Ricardo Carvalheiro (Social Sciences, 2023)
This paper analyzes the processes of racialization in Portuguese right-wing political movements through two prominent nationalist fanpages. It employs a mixed-methods approach that includes both quantitative and qualitative official data. The sample covers 72 months, from January 2017 to December 2020, encompassing a total of 3670 posts on Facebook. The main findings reveal that the fanpages utilize different discursive strategies, sometimes focusing on publishing static images and other times on sharing news links. From these publications, the fanpages garnered more than 1.4 million interactions, demonstrating consistent growth in their follower bases over the years. Emotional responses played a significant role in the interactions, particularly with Love, Sad, and Angry reactions standing out. The results also reveal that Portuguese nationalism maintains a dual ideology concerning race: ethno-exclusivism and ethno-pluralism. This observation affirms the dual nature of nationalist fanpages, where narrative elements converge and diverge based on the intended goal. Thus, individuals from Africa and Afro-descendants can be portrayed as both national heroes and social scum.